A selective role for α3 subunit glycine receptors in inflammatory pain - Harvey, Victoria L.; Caley, Alex; Müller, Ulricke C.; Harvey, Robert J.; Dickenson, Anthony H. (Frontiers in Molecular Neuroscience, 2009)
GlyR α3 has previously been found to play a critical role in pain hypersensitivity following spinal PGE2 injection, complete Freund’s adjuvant (CFA) and zymosan induced peripheral inflammation. In this study, although all models displayed typical phenotypic behaviours, no significant differences were observed when comparing the pain behaviours of Glra3-/- and wild-type littermates following the injection of capsaicin, carrageenan, kaolin/ carrageenan or monosodium iodoacetate, models of rheumatoid and osteoarthritis, respectively. However, clear differences were observed following CFA injection (p < 0.01). No significant differences were observed in the pain behaviours of Glra3-/- and wild-type littermates following experimentally induced neuropathic pain (partial sciatic nerve ligation). Similarly, Glra3-/- and wild-type littermates displayed indistinguishable visceromotor responses to colorectal distension (a model of visceral pain) and in vivo spinal cord dorsal horn electrophysiology revealed no differences in responses to multimodal suprathreshold stimuli, intensities which equate to higher pain scores such as those reported in the clinic. These data suggest that apart from its clear role in CFA- and zymosan-induced pain sensitisation, hypersensitivity associated with other models of inflammation, neuropathy and visceral disturbances involves mechanisms other than the EP2 receptor - GlyR α3 pathway.